Evaluation of Salinity, Sodicity and Fertility Indices of Soils of South-Eastern Jodhpur (Rajasthan), India: Salinity, sodicity and fertility indices of soils - Bijarnia, Shankar Lal; Singh, Ranjeet; Godara, A.S.; Jakhar, R.K.; Meena, Deshraj; Damor, Kishan; Bijarnia, Harish Kumar; Meena, R. L. (Journal of Soil Salinity and Water Quality, 2025)
The periodically diagnosis and subsequent management of salinity, sodicity and fertility status of the soils is of vital significance. The detailed systematic information about these aspects is not yet available for this tract which is essential for sustainable natural resource management. Therefore, an urgent need was felt for extensive and well planned study of soils both in the field and laboratory was conducted to evaluate salinity, sodicity and fertility indices of both irrigated and unirrigated cultivated soils of south eastern part of Jodhpur district of Rajasthan during December, 2021. One hundred sixty five composite soil samples (0-15 cm depth) from fields irrigating with tube wells/open wells water and sixty three composite soil samples (0-15 cm depth) from adjacent unirrigated fields were collected. Underground water for irrigation in the study area were good (40.66%), marginally saline (29.67%), saline (1.10%), high SAR saline (26.92%) and highly alkali (1.65%) types. The computed values of salinity and sodicity indices were 1.96, 2.86 and 1.06, 2.49 for irrigated and unirrigated soils of study area, respectively. The calculated values of fertility index for organic carbon, available phosphorus and potassium were 1.08, 1.37 and 2.50 for irrigated and 1.00, 1.17 and 2.16 for unirrigated soils, respectively. On the basis of soil and water characteristics studied it can be inferred that poor fertility, very slight salinity and moderate sodicity of soils and marginally saline, saline, high SAR saline and highly alkali underground water for irrigation were the principle constraints affecting crop production in the study area.